Comparison of Lifestyle of Catholics and Seventh-Day Adventists and the Relationship with Homocysteine as Risk Factor for Cardiovascular Diseases, a Cross-Sectional Study in Polish Males and Females - Majda, Anna (Int J Environ Res Public Health, 2021)
Background: A review of epidemiological data demonstrates relationships between defined health behaviours linked with religious affiliation and a reduced risk of developing and dying from Cardiovascular Disease (CVD). The aim of the study was to compare the lifestyle of Seventh-day Adventists (SDA) and Catholics (CA), to determine the relationship between the lifestyle of SDA, CA and the level of serum homocysteine as a risk factor for CVD. Methods: A cross-sectional study was conducted on 252 SDA and CA. The following tools were used: interview questionnaire, anthropometric measurement, the International Physical Activity Questionnaire (IPAQ), the Inventory of Health Behaviours (IHB), the Perceived Stress Scale (PSS-10), laboratory tests (homocysteine level), and the Fagerström Test for Nicotine Dependence (FTND). Results: Selected lifestyle elements, such as smoking cigarettes, drinking alcohol, physical activity, diet, Body Mass Index (BMI), health behaviours on the IHB, psychosocial factors and level of stress for CA were significantly different in comparison to SDA. The religion professed by the respondents was not significantly associated with the increased level of homocysteine as a risk factor for cardiovascular diseases (CVD). The level of homocysteine for CA were significantly different in comparison to SDA. The studied group of CA was significantly influenced by socio-demographic factors: gender, age, education, place of residence, BMI and lifestyle: drinking alcohol and smoking cigarettes, consumption of dark bread, pasta, and groats. For the studied group of SDA, the level of homocysteine was significantly influenced by socio-demographic factors such as gender, age, professional activity, and consumption of legumes. Conclusions: Public health professionals and nurses should develop culturally specific educational interventions.